Counseling, health check-up, and nutritional status to improve nutritional health at Al-Fitrah Islamic Boarding School - Hotimah Masdan Salim; Choirotussannijah Choirotussannijah; Devyana Dyah Wulandari; Nanik Handayani; Dewi Masitah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Islamic boarding schools are places of learning for students who focus on Islamic religious education. One of them is the Assalafi Al Fitrah Islamic Boarding School located in the city of Surabaya, with approximately 3,344 students. Based on demographic analysis and the origin of students from various groups, awareness about food security and nutritional health is still lacking and has not been monitored properly. This can be seen from the situation in Islamic boarding schools where the nutritional status of students is still lacking. So, this community service aims to improve the nutritional health of adolescents through counseling, health checks, and the nutritional status of students. From the results of the community service program that has been carried out, it was found that the level of knowledge about adolescent nutrition in students was very good, with the results of the BMI examination, 25% were in normal conditions and 25% were categorized as having obesity-1 nutritional problems. The activity concludes that the level of knowledge of students about balanced nutrition is very good, but it needs to be balanced with the composition of balanced nutrition it needs every day.